2018
DOI: 10.1371/journal.pone.0196085
|View full text |Cite
|
Sign up to set email alerts
|

What does the general public understand about prevention and treatment of dementia? A systematic review of population-based surveys

Abstract: ObjectivesTo synthesise results of population surveys assessing knowledge and attitudes about prevention and treatment of dementia.MethodsMEDLINE, EMBASE, PsycINFO, and grey literature were searched for English language entries published between 2012 and May 2017. Survey questions were grouped using an inductive approach and responses were pooled.ResultsThirty-four eligible studies and four grey literature items were identified. Surveys were conducted in Europe, the US, Eastern Asia, Israel, and Australia. Nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
162
4
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(198 citation statements)
references
References 57 publications
25
162
4
7
Order By: Relevance
“…Many participants reported that dementia was a natural part of the aging process, and did not perceive dementia to be a medical problem. This replicates findings from studies in Europe, the US, East Asia, Israel, and Australia, which show that nearly half of the general public believes that dementia is a normal consequence of aging [19]. Other participants reported that dementia may be caused by untreated medical conditions such as nutritional deficiencies and syphilis, or by side effects from allopathic medications or herbal treatments.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many participants reported that dementia was a natural part of the aging process, and did not perceive dementia to be a medical problem. This replicates findings from studies in Europe, the US, East Asia, Israel, and Australia, which show that nearly half of the general public believes that dementia is a normal consequence of aging [19]. Other participants reported that dementia may be caused by untreated medical conditions such as nutritional deficiencies and syphilis, or by side effects from allopathic medications or herbal treatments.…”
Section: Discussionsupporting
confidence: 79%
“…People with dementia (PWD) gradually lose cognitive function, resulting in an inability to perform activities of daily living (ADLs) [3]. A study of hospitalized patients in Uganda over the age of 60 found that 5.5% were diagnosed with dementia, but 14% had evidence of cognitive impairment on the MMSE (score < 19), suggesting that the true prevalence of dementia may already be higher than reported [4]. Therefore the provision of effective services to the increasing numbers of individuals with dementia is a public health care priority [3].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 A recent review of population surveys from Europe, the USA, Eastern Asia (China, South Korea, Singapore), Israel and Australia found that knowledge and attitudes about prevention and treatment of dementia remain poor but may be improving over time, whilst knowledge amongst those living in low-income and middle-income countries are largely unknown. 15 Our study suggested that some Asian New Zealanders have folk explanations for the causes of dementia. Folk explanations were also reported in other international studies.…”
Section: Discussionmentioning
confidence: 62%
“…When dementia symptoms are considered by ethnic minorities as a normal part of ageing, medical help is less likely to be sought . A recent review of population surveys from Europe, the USA, Eastern Asia (China, South Korea, Singapore), Israel and Australia found that knowledge and attitudes about prevention and treatment of dementia remain poor but may be improving over time, whilst knowledge amongst those living in low‐income and middle‐income countries are largely unknown …”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, five countries were classified as belonging to the first class, only one country in the second class, 20 countries in the third class, and finally 29 countries in the fourth class. higher prevalence of AD and other dementias, medical care improvement, healthier lifestyles, industrial development, increased life expectancy, and early detection of the disease can be considered the most important causes for this different trend in this country [27].…”
Section: Resultsmentioning
confidence: 99%